Adaptation of omotenashi service standards among Indonesian internship students as floorwalkers at ANA Narita - Bertha Vallencia Hermawan; Nunuk Endah Srimulyani (Japanese Research on Linguistics, Literature, and Culture, 2026)
This study examines the process of adaptation and internalization of omotenashi values among Indonesian internship students working as floorwalkers at Narita International Airport, Japan. Previous studies on omotenashi have generally focused on professional workers, while studies highlighting internship students as subjects in the transitional phase of workplace culture learning are still limited. This study uses a qualitative approach with ethnographic methods through participatory observation and in-depth interviews during a one-year internship period (January-December 2025). The results show that the internalization of omotenashi takes place in three phases, namely adjustment, development, and internalization. In the initial stage, omotenashi is understood as a technical procedural standard, but gradually develops into a situational, reflective, and anticipatory service ethic. This process involves not only language proficiency, but also the formation of contextual sensitivity in Japan's high-context communication culture. This research positions omotenashi not as an inherent and exclusive cultural value, but as a cultural practice that can be learned and negotiated by cross-cultural individuals through continuous work interactions. These findings expand the study of Japanese work culture, intercultural adaptation, and the formation of professional identity in the context of the global service industry.